2010
DOI: 10.1089/ped.2010.0007
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Pathology of Diffuse Lung Disease in Children

Abstract: The pathologic classification of diffuse lung disease in children and adolescents has undergone revision in recent years in response to rapid developments and new discoveries in the field. A number of important advancements have been made in the last 10 years including the description of new genetic mutations causing severe lung disease in infants and children, as well as the description of new pathologic entities in infants. These recently described entities, including ABCA3 surfactant disorders, pulmonary in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 95 publications
4
48
0
4
Order By: Relevance
“…Therefore, we will concentrate on the idiopathic interstitial pneumonias, ILD associated with connective tissue diseases, alveolar hemorrhage syndromes, and hypersensitivity pneumonitis. The reader is referred to the reviews by Guillerman 4 and Dishop 5 in this issue for more specifi c radiologic and pathologic details.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we will concentrate on the idiopathic interstitial pneumonias, ILD associated with connective tissue diseases, alveolar hemorrhage syndromes, and hypersensitivity pneumonitis. The reader is referred to the reviews by Guillerman 4 and Dishop 5 in this issue for more specifi c radiologic and pathologic details.…”
Section: Introductionmentioning
confidence: 99%
“…Improvement seemed to occur guidelines for the histological diagnosis of NEHI have been developed. (23) Brody et al (9) showed that GGO in the central regions of the lungs is a characteristic finding on chest HRCT in infants with NEHI, with a sensitivity of 78% and a specificity of 100%. Five or more lobes were affected in 83% of cases in our series, and the middle lobe and the lingula were affected in all of the cases.…”
Section: Discussionmentioning
confidence: 99%
“…Lung growth abnormalities are characterized histologically by impaired alveolarization manifesting as lobular simplification with deficient alveolar vascularization and septation, reduced alveolar number, and increased alveolar size resembling emphysema (Dishop 2010). As a consequence, there is diminished total alveolar surface area and reduced pulmonary diffusing capacity relative to alveolar volume (Balinotti et al 2010).…”
Section: Growth Abnormalitiesmentioning
confidence: 99%
“…This includes ''new'' BPD, which is characterized by impaired alveolarization, but less fibrosis and airway obstruction compared to classic BPD (Bhandari and Bhandari 2009), and Wilson-Mikity syndrome, which is characterized by slowly progressive respiratory distress and cyst-like changes of the lungs developing within the first few weeks of life despite minimal respiratory support at birth (Hoepker et al 2008;Philip 2009). Growth abnormalities can also be observed in nearterm and term infants as an idiopathic disorder or in association with congenital heart disease or certain genetic disorders (Deutsch et al 2007;Dishop 2010).…”
Section: Growth Abnormalitiesmentioning
confidence: 99%